2022
DOI: 10.2478/pcssr-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Physical Education: Awareness of Physical Education Teachers

Abstract: This study investigates how physical education (PE) teachers make sense of peer bullying, which types of behaviors they associate with peer bullying, their opinions about these behaviors, and methods for preventing bullying. The study group consisted of 18 PE teachers. The interview technique was used as a qualitative research method in the study. The data obtained after one-on-one interviews were analyzed through content analysis. According to the data obtained, PE teachers are the most important variable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 66 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…Five studies provided compelling evidence of the significant correlation between physical appearance and bullying within the context of PE classes. 9 , 19 , 22 , 27 , 29 Jachyra 27 found that individuals who frequently faced regular bullying primarily due to their physical appearance. Shehu 22 reached a similar conclusion, highlighting the importance of body shape in explaining both peer aggression and victimization in the context of PE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies provided compelling evidence of the significant correlation between physical appearance and bullying within the context of PE classes. 9 , 19 , 22 , 27 , 29 Jachyra 27 found that individuals who frequently faced regular bullying primarily due to their physical appearance. Shehu 22 reached a similar conclusion, highlighting the importance of body shape in explaining both peer aggression and victimization in the context of PE.…”
Section: Resultsmentioning
confidence: 99%
“…Shehu 22 reached a similar conclusion, highlighting the importance of body shape in explaining both peer aggression and victimization in the context of PE. Sağin 9 further highlighted that students who deviate from the perceived norm of physique, including being overweight, too thin, too tall, or too short, were often targeted for bullying in PE classes. Borowiec et al 19 support the above findings by noting that students who are overweight or obese are more likely to be verbally victimized or socially excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bullying is a social concern of great public health relevance because of the social and developmental impact on those involved [ 36 , 37 , 38 ]. It is undeniable that bullying can have negative or even harmful consequences for both victims and aggressors.…”
Section: Introductionmentioning
confidence: 99%